Concept of Islamic Values in Entrepreneurship Implementation: Konsep Nilai-Nilai Islami dalam Implementasi Kewirausahaan - Aeni, Umdatul; Nurhayati, Eka; Zakiyah, Ummu; Nisa, Zahrotun; Arifin, M. Syamsul; Muryadi, Muryadi; Rahmawati, Imelda Dian (Universitas Muhammadiyah Sidoarjo, 2024)
This research delves into the concept of entrepreneurship within Islamic principles, viewing it as a form of worship and a means to enhance the economy of Muslims. Employing a library research method, the study explores the Islamic perspective on entrepreneurship and its implications for economic development. It reveals that entrepreneurship, when aligned with Islamic law, is seen as obedience to Allah's commands and is highly recommended. Entrepreneurs, guided by Islamic values, demonstrate piety, integrity, and good service, with their actions driven by intentions to please Allah. The study underscores the significance of ethical entrepreneurship in promoting economic prosperity while adhering to religious principles.Highlights: Entrepreneurship as worship: Islam sees entrepreneurship as a form of worship, promoting economic improvement through ethical business practices. Ethical values: Islamic entrepreneurship emphasizes piety, integrity, and good service, reflecting moral principles in business. Success through adherence: Entrepreneurs following Islamic law seek success by ethical means, driven by intentions to please Allah and contribute positively to society. Keywords: Entrepreneurship, Value, Islam